Hospice Experience of Care Survey Development and Field Test - Price, Rebecca Anhang (RAND Corporation, 2014)
The Centers for Medicare & Medicaid Services (CMS) plans to implement a new Hospice Experience of Care Survey. This report describes the survey development process, the field test design and procedures, analytic methods and findings from the field test, and the final survey instrument for national implementation.